Comparing the experience of five major emigration countries - Castles, S (International Migration Institute, 2007)
This paper summarises and compares the findings of studies of five major emigration countries – India, Mexico, Morocco, the Philippines and Turkey. It discusses the extent to which the five countries share significant common characteristics, so that a comparative analysis may provide useful insights into migratory processes. The paper takes up the debate on migration and development that has become so prominent in international policy circles. An attempt is made to examine the extent to which migration has actually contributed to development in the five countries of origin. The general conclusion is that migration is itself a result of processes of social transformation linked to globalisation and the post-colonial re-ordering of economic and political relationships. In turn, migration becomes a factor in further processes of transformation. Thus migration should be included in strategies for achieving change, but the conditions for realising positive results are complex and difficult. Strategies of 'remittance-led development' seen simplistic and naïve. Migration alone cannot remove structural constraints to sustainable economic growth. There is a need for broadly-based long-term approaches that links the potential benefits of migration with more general strategies to reduce inequality and to improve economic infrastructure, social welfare and political governance.